Pembelajaran PjBL Berbasis Environmental-Stream untuk Meningkatkan Berpikir Kreatif pada Pembuatan Briket - Ilmi Fara Fadlika; Tri Wahyu Agustina; Asrianty Mas’ud (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to analyze the implementation of Environmental-STREAM-based Project-Based Learning (PjBL) and to examine improvements in students’ creative thinking skills regarding environmental change through the production of briquettes from coconut shell waste. The method used was a Quasi-Experimental Design with a Static Group Pretest-Posttest design. The research subjects were 46 tenth-grade students at a Madrasah Aliyah in Bandung Regency, divided into an experimental  class  (Environmental-STREAM-based PjBL)  and  a  control  class (PjBL without the Environmental-STREAM approach). The instruments used included an observation sheet for the implementation of the learning process and short-answer questions based on Torrance’s indicators of creative thinking, namely fluency, flexibility, originality, and elaboration. The results showed that the implementation of instruction achieved an average of 93.33% (teachers) and 95.00% (students), both falling into the very good category. N-gain analysis indicated that the experimental class achieved a 70.5% increase in creative thinking (high category) and the control class achieved a 43.0% increase (moderate category). The largest differences in improvement occurred in the indicators of originality (48.0%) and elaboration (37.8%), indicating that the environmental context in Environmental-STREAM-based learning can foster these two aspects of creative thinking. The conclusion of this study is that Environmental-STREAM-based PjBL can enhance students’ creative thinking, particularly in the aspects of originality and elaboration.   Keywords: Briquettes, Creative Thinking, Environmental Change, Environmental-STREAM, Project-Based Learning.